PENINGKATAN PEMAHAMAN PRINSIP-PRINSIP SYARIAH DALAM BISNIS ONLINE DIGITAL MARKETING - el ashfahany, afief; Alam, Azhar; Wulandari, Zuli; Adriansyah, Ikhwan (Abdi Psikonomi, 2022)
The community service activity aims to increase public literacy for the sharia principles in digital marketing business practice for Small, Medium and Micro Business in Makam Haji Sukoharjo and the students at the Muhammadiyah University Surakarta. This activity is conducted in the form of socialization webinars. The results of community service activity shows an increase in total understanding of 27% among respondents. The Wilcoxon Signed Rank Test result of -2.68 proves that statistically there is a difference in the level of understanding before and after the activity.